(untitled) (Third Sector Social Economic Review, 2023)
The aim of this study is to examine the effects of the education level of the adults in the household, living in a crowded household and high housing costs, which are among the determinants of child poverty in the Southern European Welfare Regime countries: Spain, Italy, Portugal, Turkey and Greece. For this purpose, selected country data for the period 2011-2022 were obtained from the Eurostat database and were analyzed by panel data analysis method using the Eviews package program. As a result of the analysis, while there was no significant relationship between child poverty and living in a crowded household in the model, a statistically significant relationship was found between child poverty and adult education and high housing costs in the household. While there is a positive relationship between high housing costs and child poverty, it is noteworthy that the positive relationship between the number of children in households with low-educated adults and child poverty confirms the literature. According to the model estimation results, one unit increase in the ratio of children living in households with low-educated adults leads to an increase of 0.20 units in the child poverty rate. A 1 unit increase in the ratio of children living in households with high housing costs increases child poverty by 0.17 units. In line with these results, it is considered as an important policy to support the costs of housing in order to increase the education level in the households where children live and to prevent child poverty.